The fool dies last - Miller, Carol, 1972- (Miller, Carol, 1972- Fortune telling mysteries., 2022)
Sisters Hope and Summer Bailey run Bailey's Boutique, a mystic shop in Asheville, North Carolina. While Hope's performing a palm reading a local doctor, Dylan Henshaw, bursts in, accusing them of trying to kill his patient with a tincture.